2022
DOI: 10.1002/chem.202104562
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Proton Transfer and Stabilizing Intermediates in Catalytic Water Oxidation via Hydrophobic Outer Sphere Interactions

Abstract: The outer coordination sphere of metalloenzyme often plays an important role in its high catalytic activity, however, this principle is rarely considered in the design of man‐made molecular catalysts. Herein, four Ru‐bda (bda=2,2′‐bipyridine‐6,6′‐dicarboxylate) based molecular water oxidation catalysts with well‐defined outer spheres are designed and synthesized. Experimental and theoretical studies showed that the hydrophobic environment around the Ru center could lead to thermodynamic stabilization of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…Along these lines, providing hydrogen-bonding interactions with suitable functional groups such as OH – in the outer coordination sphere has been shown to affect the water oxidation activity . Sun and co-workers deduced the impact of hydrophobic interactions in the outer coordination sphere on tuning the water oxidation activity . Modifying the Ru-based WOC with crown ether fragments as in 22 (Figure ) led to enhanced activity, which was attributed to changes in the water networks near the catalytic site as a result of hydrophobic interactions.…”
Section: Recent Progress In the Monitoring And Design Of Homogeneous ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Along these lines, providing hydrogen-bonding interactions with suitable functional groups such as OH – in the outer coordination sphere has been shown to affect the water oxidation activity . Sun and co-workers deduced the impact of hydrophobic interactions in the outer coordination sphere on tuning the water oxidation activity . Modifying the Ru-based WOC with crown ether fragments as in 22 (Figure ) led to enhanced activity, which was attributed to changes in the water networks near the catalytic site as a result of hydrophobic interactions.…”
Section: Recent Progress In the Monitoring And Design Of Homogeneous ...mentioning
confidence: 99%
“…820 Sun and co-workers deduced the impact of hydrophobic interactions in the outer coordination sphere on tuning the water oxidation activity. 821 Modifying the Rubased WOC with crown ether fragments as in 22 (Figure 65) led to enhanced activity, which was attributed to changes in the water networks near the catalytic site as a result of hydrophobic interactions. Recently, a new class of self-healing and regenerable WOCs were reported that attained great significance due to their long-term usage and analogous nature to the OEC where the CaMn 4 O x core is regenerated.…”
Section: Homogeneous Molecular Catalysts For the Oermentioning
confidence: 99%
“…As shown in Figure a,b, the substitution of H with D significantly decreases the J values for NF and NF/PrCH. The KIE’s value over the potential range of 1.8 to 2.0 V vs RHE is near 3, knowing the fact that the KIE’s value >1.5 indicates an O–H bond cleavage in RDS, a primary KIE (PKIE) . The NF/LaPrCH (Figure c) depicts a significant decrease in the KIE value (<1.3) at NF/LaPrCH, the first sign of accelerating PT.…”
Section: Resultsmentioning
confidence: 89%
“…12 adjusted by KOH and K 3 PO 4 (considering that the atom's proton transfer studies showed no significant dependency of J value on K 3 PO 4 ). Figure 4 93 The NF/LaPrCH (Figure 4c) depicts a significant decrease in the KIE value (<1.3) at NF/LaPrCH, the first sign of accelerating PT. The closeness of LSV measurements in Figure 4c explains how the presence of La dramatically diminishes the J value gap of the deutero and proteo solutions so that the KIE gets values lower than 1.5, a secondary KIE (SKIE), indicating no tangible O−H bond cleavage in the RDS of OER.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…To mimic the function of the adaptive architecture in PSII, conformationally flexible ligands with the ability to accommodate the structural and electronic demands of the different intermediates have been successfully applied in artificial water oxidation catalysts and have resulted in a few elegant examples of seven-coordination phenomena in Ru-bda and Ru-tda (Scheme , bda = 2,2′-bipyridine-6,6′-dicarboxylate, tda = [2,2′:6′,2″-terpyridine]-6,6″-dicarboxylate) catalysts that display enhanced activity comparable to the Mn 4 CaO x cluster of PSII. , The classic Ru-bda system mediates O–O bond formation via the interaction of two metal-oxyl species (I2M), which is highly dependent on the interaction between the catalysts . Modifications on distal ligands to preorganize the substrate water can promote an alternative water nucleophilic attack (WNA) pathway, where the preorganized water network serves as a base to facilitate the proton transfer process. Another intriguing strategy is to introduce intramolecular proton acceptors by rearrangements of the coordination conformations, which is skilfully illustrated by Ru-tda and Ru-tpa type water oxidation catalysts (Scheme , tpa = 2,2′:6′,2″-terpyridine-6,6″-diphosphonate). However, installations of proton acceptor at the second coordination sphere inevitably lead to a competitive coordination with substrate water, making it impossible to fully leverage the catalytic site. , Therefore, the coordination ability of the proton relay unit needs to be negotiated with the water molecule to lower the energy required for substrate binding and activation. , …”
Section: Introductionmentioning
confidence: 99%